Group housing increases alertness and social interaction compared to traditional single stabling in two-year-old sport horse stallions during pretraining - L. Kroschel; F. Pilger; J. Aurich; C. Nagel; C. Aurich (Animal)
Horses in training are often stabled individually, but this is increasingly questioned. We have investigated the effects of different stabling systems in Warmblood stallions during a 12-week pretraining programme. Stallions were 24 months old and housed either in a group stable (Group 24, n = 9) or in individual boxes (Box 24, n = 10), or they were 30 months of age and housed in individual boxes (Box 30, n = 10). Cortisol, heart rate, heart rate variability (HRV), body development, injuries and selected behaviour patterns were analysed (1) at transfer from pasture to stable and (2) thereafter, repeatedly during pretraining. Salivary cortisol concentration increased immediately after stabling (P < 0.001). This increase was most pronounced in Group 24 stallions (P = 0.044). A diurnal cortisol rhythm was re-established after 2–3 days, but occasional irregular increases in salivary cortisol concentration occurred in Group 24 stallions throughout the pretraining period. In response to stabling, also heart rate increased for approximately 3 h (P < 0.001) with a most pronounced rise in Group 24 stallions (time × group P < 0.001). BW decreased transiently after stabling (P < 0.001). Skin lesions were mainly superficial abrasions, and they were more frequent in group-housed vs individually stabled stallions (P < 0.001). Lying bouts were more frequent in individually housed than in group-housed stallions (P < 0.001). Mutual grooming occurred only in Group 24 stallions (group P < 0.001). Playing was seen in Group 24 stallions predominantly in the morning (time P < 0.001, group P < 0.001). Agonistic behaviour was more evident in individually housed than in group-housed stallions but was seen occasionally in individually housed stallions (group P < 0.001). Pawing the ground was mainly observed in individually housed stallions in the morning before feeding and was close to absent in the afternoons (time P < 0.001, group P < 0.001). In conclusion, cortisol concentration, heart rate, HRV and behaviour suggest that group-housed stallions, to some extent, were more challenged during the pretraining period than individually housed stallions. Under the conditions of this study, both individual and group stabling are acceptable for two- to three-year-old stallions and there was no evidence for a major advantage of one housing system over the other.